ANALISIS TEMA EKSISTENSIALISME DALAM PUISI “AKU” KARYA CHAIRIL ANWAR DENGAN PENDEKATAN STRUKTURALISME - Yulinda Saragih; Dewi Pakpahan; Miyana Dewi E. Sitepu; Alda Khafifah Ritonga; Eveline Stephani; Atika Wasilah Sipayung (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the theme of existentialism contained in Chairil Anwar’s poem “Aku” using a structuralist approach as the basis for analysis. This study employs a qualitative descriptive method using the read-and-note technique. The analysis focuses on four main structural elements: diction, imagery, rhyme and rhythm, and typography. The results of the study indicate that these four structural elements work synergistically to construct the theme of existentialism. The harsh and expressive diction reflects the lyrical persona’s rejection of collective norms. Strong physical imagery represents the inner suffering that does not halt the lyrical persona’s progress. Free rhyme reflects existential freedom, while dense and concise typography underscores the steadfastness of the stance of resistance. The theme of existentialism in this poem is not imposed from outside the text but arises from the interaction of structural elements that mutually reinforce one another. Thus, the poem “I” is a manifestation of existentialism that affirms that life is meaningful when humans dare to be themselves.